ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENERIMAAN BEASISWA DENGAN METODE SAW PADA UNIVERSITAS MUHAMMADIYAH JAMBI - Kurniawansyah, Kevin; Akbar, Zulfikri; Ediansa, Oka; AH, Hetty Rohayani. (LPPM Universitas Muhammadiyah Jambi, 2022)
Scholarships are grants in the form of financial assistance given to individuals, students or students for the continuation of education. In accordance with the program guidelines issued by the Directorate General of Higher Education, it must follow the 3T principles, namely Right Target, Right Amount and Timely. Jambi Muhamamdiyah University is one of the private universities that received a quota for the scholarship, because of the large number of scholarship recipients, the university must be selective in determining who is eligible to get the scholarship. One of the methods of information technology that can support decision-making in an organization or company is the Simple Additive Weighting (SAW) method so that it can facilitate the process of managing, sorting, comparing and selecting scholarship recipients, so as to increase the efficiency and effectiveness of the work of the actors. business. The purpose of this research is to analyze and design a prototype of the Scholarship Acceptance Decision Support System with the SAW (Simple Additive Weighting) Method at the University of Muhammadiyah Jambi so as to increase the effectiveness and efficiency in receiving scholarships and to assist in providing alternative decisions in the selection of scholarship recipients. This design was made using the visual paradigm and using object-based modeling techniques to describe the analysis and design of the system, namely in the form of use case diagrams, class diagrams, and activity diagrams. This research resulted in a prototype design of the analysis system and the design of a Scholarship Acceptance Decision Support System using the SAW (Simple Additive Weighting) method at the University of Muhammadiyah Jambi. On this basis, an integrated system is needed, it is hoped that the system can be implemented directly to increase the effectiveness and efficiency of the implementation of scholarship acceptance at the University of Muhammadiyah Jambi